Seed banks for future generation. - Chin, Hoong Fong; Quek, Paul; Sinniah, Uma Rani (Springer, 2013)
The importance of rich biological diversity in providing greater opportunities for economic development, discoveries in medicine and especially in adaptation responses to challenges such as climate change and natural disasters is receiving tremendous attention globally. One way of conserving biological materials of plants is through storage of seeds in genebanks. Presently there are 1,750 genebanks worldwide storing more than 7.4 million accessions. Mankind has also taken a giant leap in establishing the Svalbard Global Seed Vault the largest seed bank conserving seeds under permafrost conditions with a capacity of four million accessions under one roof. The challenge to date is to ensure that the seed genebanks are coordinated and properly managed in relation to maintenance of viability, characterization with systems that are user friendly and finally is accessible for utilization when necessary. This chapter introduces the importance of having genebanks and how the genebanks are observed as an insurance policy. It explains the biology of seeds and factors which promote seed longevity. The importance of understanding the nature of the seed to be stored is discussed in relation to orthodox, recalcitrant and intermediate seeds. The method suitable for different kind of seeds such as cryogenic storage for recalcitrant and intermediate seeds is mentioned. The role and types of seed banks, national, regional and international as well as a genebank of single crop or multiple crops is discussed. Finally a discussion on issues in seed banks management in general.